Examination of the Effect of Pre-Hsg Melatonin on Endometrial Ablation and Uterine Dysplasic Cell Development Associated with Radiation - Sapmaz, Ekrem; Akpolat, Nusret (Fırat University, 2012)
Objective: To examine the effect of X ray, lipiodol and melatonin used during HSG on hystopathologic changes in the rat uterus. Material and Method: A total of 40 Spraque-Dawley type female rats were randomly allocated to 4 groups. Group 1 (n=10): Abdomen was opened and closed without X-ray exposure, group 3 (n=10): X-ray exposure, group 3 (n=10): Abdomen was opened and 0.1 ml Lipiodol was applied to each uterine horn, group 4 (n=10): 10 mg/kg/ip melatonin was administered and 15 minutes later, 0.1 ml Lipiodol was applied to each uterine horn. The rats in group 2, group 3 and group 4 were exposed to 3 doses of X-ray with 2-minute intervals after the closing of the abdomen (total dose = 15-20 milli Rad). The abdomen was opened 3 hours later in all rats. Uterine horn was removed and fixated in 10% formaldehyde. The preparations were examined under a light microscope to evaluate hystopathologic changes. Kruskal Wallis variance analysis was used of data. Results: Endometrial ablation was found similar in all groups. Dysplasic changes and congestion were established to be significantly elevated in group 2, when compared to other groups (p

Amaç: Histerosalpingografi esnasında kullanılan X ray, lipiodol ve melatoninin rat uterusunda endometriyal ablasyon, uterus luminal hücrelerinde displazik değişiklikler ve myometrial liflerde iğsi yapılaşma üzerine etkisinin incelenmesi. Gereç ve Yöntem: 40 adet Sprage Dawley cinsi dişi rat, rastgele 4 gruba ayrıldı. Grup 1 (n=10): Batın açılıp kapatılan ve X ray uygulanmayan grup, grup 2 (n=10): X ray uygulanan grup, grup 3 (n=10): Batın açılıp her bir uterin horna 0.1 ml Lipiodol uygulanan grup, grup 4 (n=10): 10 mg/kg/ip melatonin uygulanıp, 15 dakika sonra her bir uterin horna 0.1 ml Lipiodol uygulanan grup. Batınları kapatılan Grup 2, grup 3 ve grup 4'teki ratlara 2 şer dakika ara ile 3 doz X ray uygulandı (Toplam doz=15-20 mili Rad). Tüm ratların 3 saat sonra batını açıldı. Sol uterin horn çıkarıldı. %10'luk formaldehitle tespit edildi. Işık mikroskopisinde endometrial ablasyon, fibrozis, endometrial bezlerdeki dejenerasyon, konjesyon ve ablasyondan sonra kalan, en üst uterin tabakadaki hücrelerde displazik değişiklikler ve myometriyumda iğsi yapılaşma incelendi. İstatistiksel analiz için Kruskal Wallis Varyans analizi kullanıldı. p0.05). Uterusdaki luminal displazik değişiklikler ve konjesyon grup 2'de diğer gruplara nazaran anlamlı olarak artmış idi (p
HSG Öncesi Kullanılan Melatoninin Radyasyona Bağlı Gelişecek Endometriyal Ablasyon ve Uterin Displazik Hücre Gelişimi Üzerine Etkisinin İncelenmesi